Kupieckie ogłoszenia prasowe zamieszczane w „Dzienniku Bydgoskim” z lat 1907–1914 – rekonesans badawczy - Rypel, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The aim of this article is to explain the specificity of Bydgoszcz merchants’ mercantile discourse at the beginning of 20th century. It was time of rapid industrialization and economic changes. Advertisements not only met Bydgoszcz inhabitants’ needs but also started to create them. However, “Dziennik Bydgoski” documents keeping mercantile traditions. Published advertisements usually refer to an old model of informational announcement that was usually consisted of a specific offer in the form of a list of offered goods. Company owner’s name was the only quality assurance. Another popular form of advertising had a form of a short letter, where the merchant talked directly to their potential clients. Basic strategies used in this kind of advertisement were based on expressing respect to the customer and offering additional service. But the most characteristic feature of mentioned advertisements was appealing to patriotic feelings of customers. Encouraging people to buy in Polish shops and placing ads of Polish merchants was a form of resistance against growing Germanization in Bydgoszcz. This feature of the announcements published in “Dziennik Bydgoski” distinguish them from advertisements printed in Polish newspapers in Polish Kingdom and Galicia.